Production and manufacturing system management coordination approaches and multi-site planning - Renna, P. (Engineering Science Reference, 2013)
"This book presents relevant theoretical frameworks and most recent research findings in this area, providing significant theories for research students and scholars to carry out their continuous research as well as practitioners who aim to improve upon their understanding of distributed production planning"--Provided by publisher.
Keywords: Business logistics.; Industrial management.; elektronické knihy; electronic books